Joint and Bone Exercises to Prevent Osteoporosis in the Elderly at the Tresna Werdha I Budi Mulya Social Home - Larasati, Rahma Ayu; Farsida, Farsida; Handayani, Tutwuri; harlyana, cyntya; Sugiharto, Gatot; Insyiera, Nayla (Abdi Masyarakat, 2023)
Osteoporosis is a major non-communicable disease and the most common bone disease, affecting one in three women and one in five men over the age of 50 worldwide. The clinical consequence of osteoporosis is fragility fractures. With the rapid ageing of the population worldwide and the changes in lifestyle habits, the incidence of osteoporosis and related fractures has significantly increased and will continue to increase markedly in the future. Exercises such as walking, dancing, low-impact aerobics work directly on bones in the legs, hips and lower spine to slow bone loss. We provide osteoporosis prevention education to the elderly in nursing homes as an effort to prevent osteoporosis. We also provide training on joint and bone exercises to prevent osteoporosis.